Immune Response to Therapeutic Staphylococcal Bacteriophages in Mammals: Kinetics of Induction, Immunogenic Structural Proteins, Natural and Induced Antibodies - Kaźmierczak, Zuzanna; Majewska, Joanna; Miernikiewicz, Paulina; Międzybrodzki, Ryszard; Nowak, Sylwia; Harhala, Marek; Lecion, Dorota; Kęska, Weronika; Owczarek, Barbara; Ciekot, Jarosław; Drab, Marek; Kędzierski, Paweł; et al. (Frontiers in Immunology, 2021)
Bacteriophages are able to affect the human immune system. Phage-specific antibodies are considered as major factors shaping phage pharmacokinetics and bioavailability. So far, general knowledge of phage antigenicity nevertheless remains extremely limited. Here we present comparative studies of immunogenicity in two therapeutic bacteriophages, A3R and 676Z, active against Staphylococcus aureus, routinely applied in patients at the Phage Therapy Unit, Poland. Comparison of the overall ability of whole phages to induce specific antibodies in a murine model revealed typical kinetics of IgM and IgG induction by these two phages. In further studies we identified the location of four phage proteins in the virions, with the focus on the external capsid head (Mcp) or tail sheath (TmpH) or an unidentified precise location (ORF059 and ORF096), and we confirmed their role as structural proteins of these viruses. Next, we compared the immune response elicited by these proteins after phage administration in mice. Similar to that in T4 phage, Mcp was the major element of the capsid that induced specific antibodies. Studies of protein-specific sera revealed that antibodies specific to ORF096 were able to neutralize antibacterial activity of the phages. In humans (population level), none of the studied proteins plays a particular role in the induction of specific antibodies; thus none potentially affects in a particular way the effectiveness of A3R and 676Z. Also in patients subjected to phage therapy, we did not observe increased specific immune responses to the investigated proteins.